Modeling the growth rates of potential forestry species in Rwanda: a tree structural traits-based approach - Resetar,Lucija (Student thesis series INES, 2025)
Forest plantations play a crucial role in the livelihoods of Rwandan people. They provide valuable wood resources, such as timber and biomass energy. The first plantations created in the colonial period from 1920 to 1948 contained only exotic Eucalyptus species, which is thought to out-perform native species in terms of more rapid wood production. Over time, this resulted in the domination of non-native species in forest plantations across Rwanda, primarily Eucalyptus species. However, replacing native species with monocultures of the exotic ones impacts the local environment in multiple negative ways. Therefore, more sustainable forestry practices are needed, such as indigenous species planting. Modeling the performance of potential Rwandan forestry species may serve as a useful tool for forest management strategies. Thus, dynamic vegetation model LPJ-GUESS was used in this study, with the aim to try and adjust the model so that it can represent the growth of five species interesting for the context of Rwandan forestry: Eucalyptus microcorys, Eucalyptus citriodora, Grevillea robusta, Entandrophragma excelsum and Polyscias fulva. Since tree performance essentially depends on their functional traits, with structural traits playing a key role, this study tried to determine the extent up to which structural tree traits can explain the differences in growth rates between potential forestry species in Rwanda. Specifically: wood density, sapwood turnover rate, tree crown area to diameter at breast height (DBH) and tree height to DBH allometric parameters, specific leaf area and leaf area to sapwood area ratio. The impact of several additional functional traits on growth was examined as well, to help explain remaining growth differences not captured by the structural traits alone. Differences between the growth of the modeled species due to the species-specific structural traits were evident. Still, these traits could explain only a fraction of the modeled differences, leaving much unexplained when comparing to the observed differences in growth. Of all the additional functional traits examined, maintenance respiration coefficient had the strongest influence on the growth patterns. The outcomes of this study provide valuable insights in species-level tree growth modeling and could thus potentially help in applying more sustainable forest management practices in Rwanda.
Keywords: Physical Geography; Ecosystem Analysis; Eucalyptus; Exotic Species; Native Species; Structural Traits; Ecosystem Modeling; Rwanda; Forestry